2007
DOI: 10.1128/iai.00551-07
|View full text |Cite
|
Sign up to set email alerts
|

Protective Properties and Surface Localization ofPlasmodium falciparumEnolase

Abstract: The enolase protein of the human malarial parasite Plasmodium falciparum has recently been characterized. Apart from its glycolytic function, enolase has also been shown to possess antigenic properties and to be present on the cell wall of certain invasive organisms, such as Candida albicans. In order to assess whether enolase of P. falciparum is also antigenic, sera from residents of a region of Eastern India where malaria is endemic were tested against the recombinant P. falciparum enolase (r-Pfen) protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 58 publications
6
74
0
Order By: Relevance
“…One of these, enolase, is of interest because it has recently been shown to be expressed at the surface of the merozoite and has been implicated similar to aldolase to perform some "moonlighting" function during invasion (26,27). In W2mef, there also appears to be increased expression of proteins that are exported to the cytosol from the infected erythrocyte (Table II).…”
Section: Comparison Of W2mef and W2mef/nm Merozoite Proteinmentioning
confidence: 96%
“…One of these, enolase, is of interest because it has recently been shown to be expressed at the surface of the merozoite and has been implicated similar to aldolase to perform some "moonlighting" function during invasion (26,27). In W2mef, there also appears to be increased expression of proteins that are exported to the cytosol from the infected erythrocyte (Table II).…”
Section: Comparison Of W2mef and W2mef/nm Merozoite Proteinmentioning
confidence: 96%
“…Also it has been demonstrated that enolase is an essential protein in fungal metabolism (27), and its lack of expression may cause delays in larval development (28). Apart from its glycolytic function, enolase has also been shown to possess antigenic properties and to be present on the cell wall of certain invasive organisms, such as Candida albicans (29). In addition, it has been found that enolase levels are highly elevated in malaria parasite-infected red blood cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…L-LDH, which is a possible drug target in malaria, was also found in the clinical ring stages [21,22]. Parasite enolase, which is thought to be exported to the infected erythrocyte surface [23], was also expressed in the clinical ring stages. Many other metabolic enzymes are detected in the ring-stage clinical isolates.…”
Section: S-adenosyl Homocysteinasementioning
confidence: 96%